2002
DOI: 10.1042/bj20020153
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glucose on the potency of two distinct glycogen phosphorylase inhibitors

Abstract: Two distinct glycogen phosphorylase inhibitors, 5-chloro-1H-indole-2-carboxylic acid [1-(4-fluorobenzyl)-2-(4-hydroxy-piperidin-1-yl)-2-oxoethyl]amide (CP-320,626) and 1,4-dideoxy-1,4-D-arabinitol (DAB), were characterized in vitro with respect to the influence of glucose on their potencies. CP-320,626 has previously been shown to bind to a newly characterized indole site, whereas DAB seems to act as a glucose analogue, but with slightly different properties from those of glucose. When analysed in pig liver gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…As noradrenaline promotes glycogenolysis (Magistretti, 1988;Subbarao and Hertz, 1990;Sorg and Magistretti, 1991;Coopersmith and Leon, 1995), the action of b-AR agonists b-ARs in central metabolism and memory ME Gibbs et al was challenged with the glycogen phosphorylase inhibitor DAB that prevents glycogen breakdown (Andersen et al, 1999;Andersen and Westergaard, 2002). We have shown that administration of DAB interferes with memory processing (Gibbs et al, 2006a).…”
Section: -Ar Agonists Affect Memory Formation By Activating Glycogenomentioning
confidence: 87%
“…As noradrenaline promotes glycogenolysis (Magistretti, 1988;Subbarao and Hertz, 1990;Sorg and Magistretti, 1991;Coopersmith and Leon, 1995), the action of b-AR agonists b-ARs in central metabolism and memory ME Gibbs et al was challenged with the glycogen phosphorylase inhibitor DAB that prevents glycogen breakdown (Andersen et al, 1999;Andersen and Westergaard, 2002). We have shown that administration of DAB interferes with memory processing (Gibbs et al, 2006a).…”
Section: -Ar Agonists Affect Memory Formation By Activating Glycogenomentioning
confidence: 87%
“…To explore this possibility, the enzymatic activity of PYGM was measured as described under "Experimental Procedures" (41,42). Briefly, the glucose 1-phosphate produced by PYGM is converted to glucose 6-phosphate by the enzyme phosphoglucomutase.…”
Section: Resultsmentioning
confidence: 99%
“…Activity Assay for Glycogen Phosphorylase-A glycogen phosphorylase activity assay was performed as indicated (41,42) with some modifications. Briefly, cells were washed twice with cold PBS and resuspended in 500 l of TES buffer (20 mM Tris, pH 7.4, 1 mM EDTA, 225 mM sucrose, 2.5 mM DTT, 0.1 mM PMSF, 1 g/ml leupeptin, 1 g/ml aprotinin).…”
Section: Methodsmentioning
confidence: 99%
“…The substituent effects of hydroxyl/methoxy groups in the 4Ј-cinnamyl derivatives (13)(14)(15) were quite different from those of phenethylphenylphthalimide derivatives, i.e., the GPa-inhibitory activity decreased in the order of: non-substitutedϾdimethoxyϾdihydroxy derivatives [13Ͼ14ϭ15].…”
Section: Resultsmentioning
confidence: 99%
“…1), which has been used widely as a commercially available control compound for the structural development studies of GP-inhibitors. [12][13][14] DAB (2) inhibits hepatic glycogen breakdown in vivo and has an anti-hyperglycemic effect, which was found to be most pronounced in obese mice. 12) We have been engaged in the creation of bioactive compounds based on multi-template approach utilizing thalidomide (3) (Fig.…”
mentioning
confidence: 99%